Low pH anaerobic digestion of waste activated sludge for enhanced phosphorous release. (15th September 2015) - Latif, Muhammad A.; Mehta, Chirag M.; Batstone, Damien J.
Abstract: This paper assesses anaerobic digestion of waste activated sludge (WAS) at low pH to enhance phosphorous solubility. Batch biochemical methane potential tests were conducted at a pH range of 5 to 7.2 in two separate sets (two different WAS samples collected from municipal WWTP). Low pH (<5.7) caused a significant (p = 0.004) decrease in methane potential ( B 0 ) up to 33% and 3.6 times increase in phosphorus release compared to neutral pH (7–7.7), but with no major change in methane production rate coefficient ( k hyd ). The loss in methane yield was mainly due to decrease in hydrolytic capability rather than inhibition of methanogenesis with volatile fatty acids being <300 mgCOD L −1 and soluble COD <1300 mgCOD L −1 even at low pH. While pH did not influence the acetoclastic community (Methanosaeta dominated), it was the primary driver for the remaining community (p = 0.004), and caused a loss of diversity and shift to Clostridia. Graphical abstract: Highlights: Preventing phosphorous binding by low pH AD can enable resource recovery. A decrease in CH4 yield at low pH caused decrease in particulates solubilization. No change in kinetics at low pH. Bacterial community influenced by pH but not acetoclastic methanogens. Multi-stage AD with an intermediary struvite recovery could avoid methane loss.